Studi Farmakoepidemiologi Vitamin Penambah Darah pada Ibu Hamil di Kecamatan Jatinangor - Irma Rismayanti Amanah; Irma Rismayanti Amanah (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Introduction: The prevalence of iron deficiency anemia in pregnant women in the world according to WHO ranges from 35-37%, similarly found in pregnant women in Indonesia, Riskesdas in 2013 reported a prevalence of 37.1%. Although the treatment of iron deficiency anemia for pregnant women has been entered into ANC treatment, the prevalence has not given the expected thing. However, in Sumedang District, the prevalence of anemia in pregnant women in 2016 lower, 9.69%, pharmacoepidemiological data related to the use of blood boosting vitamins in Jatinangor is still limited. this research was conducted in Jatinangor as target area of Universitas Padjadjaran.Objective: To know the blood Enhancer supplement consumption practices on pregnant women in Jatinangor.Methods: A cross-sectional study was carried out in July-August 2018 with pregnant women in Jatinangor, based on the formula large sample descriptive, sampling conducted in 12 villages and subjects were selected consecutively. Data analysis was carried out descriptively interview data using a closed questionnaire.Results: within research recorded 532 pregnant woman, 110 pregnant women are eligible to participate. It was found 96 pregnant women taking blood boosting vitamins, 69 Taking folicacid, 27 taking irontablets, 15 consuming B12, 2 consuming B6. It was found who did not take vitamins, 14 pregnant women for several reasons, 8 people felt healthy, 3 people felt the complaints were mild so it does not require vitamins, 4 others were afraid of the side effects.Conclusion: Most of the respondents already know how to consume suplments